2014
DOI: 10.1186/s12888-014-0379-4
|View full text |Cite
|
Sign up to set email alerts
|

Sustained improvements in students’ mental health literacy with use of a mental health curriculum in Canadian schools

Abstract: BackgroundEnhancement of mental health literacy for youth is a focus of increasing interest for mental health professionals and educators alike. Schools are an ideal site for addressing mental health literacy in young people. Currently, there is limited evidence regarding the impact of curriculum-based interventions within high school settings. We examined the effect of a high-school mental health curriculum (The Guide) in enhancing mental health literacy in Canadian schools.MethodsWe conducted a secondary ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
151
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(170 citation statements)
references
References 40 publications
15
151
0
4
Order By: Relevance
“…Additionally, previous research has demonstrated that classroom teachers' application of the resource in their own classrooms, without the addition of external mental health interventions, significantly and substantively improved students' mental health knowledge and attitudes, and that these positive results were sustained over time. 17,28 This approach differs from other types of interventions that use mental health experts as in school educators 45,46 and from standalone programs that are not designed to be embedded into school curriculum, are not based on existing teaching methods used in schools, and do not concurrently address teacher and student MHL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, previous research has demonstrated that classroom teachers' application of the resource in their own classrooms, without the addition of external mental health interventions, significantly and substantively improved students' mental health knowledge and attitudes, and that these positive results were sustained over time. 17,28 This approach differs from other types of interventions that use mental health experts as in school educators 45,46 and from standalone programs that are not designed to be embedded into school curriculum, are not based on existing teaching methods used in schools, and do not concurrently address teacher and student MHL.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23] As most mental disorders occurring over the lifespan can be identified by age 25, it is necessary to enhance MHL in young people to help improve their potential for good mental health outcomes. 18,21,[23][24][25][26][27][28] Schools provide the ideal location in which to implement interventions that can be demonstrated to improve MHL. [14][15][16]23,[29][30][31][32][33][34][35] Early definitions of MHL, as "knowledge and belief about mental disorders which aid their recognition, management, and prevention," 19, p 182 have evolved concurrently with advances in understanding of health literacy, [36][37][38][39] including incorporation of constructs pertaining to stigma, advocacy, and help seeking, 20,21 and empowerment.…”
Section: Limitationsmentioning
confidence: 99%
“…These recommendations are in good alignment with a recent MHL approach that is based on existing classroom friendly pedagogical applications that can be easily and inexpensively delivered within existing educational systems and does not require extracurricular or outside-of-school inputs [2,6]. When applied through enhancing capacity of classroom teachers to integrate evidence-based MHL curriculum resources (http://teenmentalhealth.org/curriculum/) into existing curriculum, as demonstrated by numerous Canadian studies, such interventions can concurrently result in positive MHL outcomes for both students and teachers alike [21][22][23][24]. Additionally, this approach can facilitate the development of an horizontally integrated school-based pathway to youth mental health care that links education and health systems, enhances identification, and facilitates triage and referral of students with mental disorders to local mental health care providers, thus functionally integrating educational and health care delivery systems, even in the absence of specific policies designed to do so [13,25].…”
mentioning
confidence: 99%
“…The life improvement metrics in this study extend beyond usual measures of MHL applied in other research [22,35,38] and provide an additional and wider ranging assessment of the impact of a school based MHL intervention. The teacher reported improvements in students' at-school behaviour and mental health care related helpseeking behaviour suggests that the mental health curriculum resource (AGMv) embedded and applied in schools may have the potential to lead to wider improvements in students' health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The school component of the program applies a culturally and contextually modified MHL curriculum (the Guide) which has undergone substantial field testing and research in Canada, demonstrating significant and substantial positive impacts in both student and teacher MHL [22,[33][34][35]. The Guide is made up of a teachers' self-evaluation test, a teachers' mental health knowledge selfstudy guide and six classroom ready modules, including: the stigma of mental illness; understanding mental health and wellness; information about specific mental illnesses; experiences of mental illness; seeking help and finding support; and the importance of positive mental health.…”
Section: Introductionmentioning
confidence: 99%